DEVELOPMENT OF HISTORICAL UNO CARD LEARNING MEDIA TO INCREASE STUDENTS' LEARNING MOTIVATION ON THE MATERIAL OF COLONIALISM AND INDONESIAN RESISTANCE FOR CLASS XI SMAIT AL FITYAH PEKANBARU: Pengembangan Media Pembelajaran Kartu Uno Sejarah Untuk Meningkatkan Motivasi Belajar Siswa Pada Materi Kolonialisme dan Perlawanan Bangsa Indonesia Kelas XI SMAIT Al Fityah Pekanbaru - Nur; Isjoni Ishaq; Asril (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Learning media is vital for school education, yet history lessons often suffer from low student motivation due to traditional narrative methods. An innovative solution is the development of modified History Uno cards, featuring clear text on relevant topics, evaluation questions, and engaging illustrations to boost interactivity and motivation. This media was created using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), ensuring a systematic process aligned with student needs and learning goals. The primary aims are to enhance history learning motivation, offer an interactive alternative via Uno cards, and facilitate easier comprehension for students at SMAIT Al Fityah Pekanbaru. Expert validation yielded 86% approval from media specialists and 92% from material experts.